Pengaruh Inflasi, Suku Bunga Bank Indonesia, dan Nilai Tukar Rupiah terhadap Pendapatan Margin Murabahah - Nourma; Budiman, Mochammad Arif (Indonesian Journal of Applied Accounting and Finance, 2024)
Murabahah financing is one of the financing that is most sought after by the public in sharia banking, making it very important in sharia banking operations. The aim of this research is to determine the importance of understanding macroeconomic factors that influence the financial performance of sharia banking, especially in murabahah financing schemes, including inflation, interest rates and the rupiah exchange rate at PT. Bank Syariah Indonesia (BSI). The data used in this research is quantitative secondary data. The data was obtained from trusted sources, namely the Central Statistics Agency (BPS), Bank Indonesia (BI), the Ministry of Trade, and BSI's monthly murabahah margin income report from February 2021 to December 2023 for 35 months taken via the BSI website. Data analysis techniques used in this research are the classical assumption test, multiple linear regression test and hypothesis test. The research results show that partially (T test), the variables inflation and the rupiah exchange rate do not have a significant effect on murabahah margin income with inflation significance. amounted to 0.316 and the rupiah exchange rate amounted to 0.870. Meanwhile, the Bank Indonesia interest rate variable partially has a significant effect on murabahah margin income with sig. 0,000. Simultaneously (F Test) inflation, Bank Indonesia interest rates and the rupiah exchange rate have a positive effect on murabahah margin income with sig. 0,000. The findings of this research contribute to knowledge for sharia banking regarding the impact of macroeconomic factors that can influence profit income, especially at Bank Syariah Indonesia.